DAYA TARIK KUALITAS BRAND QONITA BATIK PEKALONGAN - Safira Salma Sania; Hendri Hermawan Adinugraha (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2021)
Facts about developments in industry, which in the city of Pekalongan itself is famous for its Batik and has become a trend in the fashion world. So the purpose of this study is to determine the attractiveness of the products contained in Qonita Batik Pekalongan. One of the famous shopping centers in Pekalongan city and in other cities is Qonita Batik Pekalongan. This research is a qualitative approach research with descriptive mode data type with data collection techniques in this study using interviews, documentation, and observation. Qonita Batik products have their own charm so that users feel satisfied or feel comfortable using these products including quality, design, and brand. The appeal of Qonita Batik products that are used as modern fashion with their traditional characteristics lies in the undoubted quality of the products.